Evaluation of the Gonosticon Dri Dot Test in Females with a Low Incidence of Gonorrhea - Dyckman, John D. (1974)
A group of 765 females attending a Planned Parenthood Clinic was screened for gonorrhea by inoculating Thayer-Martin plates and Transgrow bottles with specimens from the cervix. Blood was obtained at the same time and tested for anti-gonococcal antibody by using the Gonosticon Dri Dot test. In this low-incidence group, 18 positive cultures were detected by culture on Thayer-Martin plates, whereas Transgrow detected only 15 positive cultures. Of the 18 patients with gonorrhea, 11 exhibited reactive serum (agglutination of the latex particles). In the total population, 64% of the patients had nonreactive serum (no agglutination) and negative cultures; 25% had reactive serum and negative cultures. When this latter group was subdivided on the basis of race, blacks and Latin Americans were found to have a higher incidence of reactive serum with a corresponding negative culture than was found in whites. Patients who were originally culture positive and nonreactive in the Gonosticon Test were retested; three out of four patients retested within 6 to 11 days after the initial screening had converted to a positive Gonosticon test.